MODELS FOR GROWTH CHARACTERISTICS AND THEIR APPLICATIONS IN YIELD STUDIES FOR Pinus caribaea Morelet 1851 IN SOUTHWESTERN NIGERIA (2014)
Development of empirical models provides ample prospects of exploring established mathematical theories and relationships among tree growth variables for sustainable forest management options. However, there is inadequate information on modelling growth characteristics and productivity potentials of Pinus caribaea, a pulpwood species which is now being proposed for timber production in Nigeria. Hence, models for growth characteristics and their applications in yield studies for Pinus caribaea in southwestern Nigeria were investigated. Sixty Temporary Sample Plots (TSPs) of size 20m x 20m each and of different Age (A) series based on stocking density were sampled from Omo Forest Reserve (n=16 TSPs -15 and 21 years), Oluwa Forest Reserve (n=36 TSPs-18, 20, 35, 36 and 37 years) and Shasha Forest Reserve (n=8TSPs-27years) in Ogun, Ondo and Osun States respectively using stratified random sampling method. Growth variables: Diameter at Breast Height (DBH), Stem Quality (SQ) and Total Height (THT) were measured in each plot and Basal Area (BA), Stem Volume (SV), Tree Slenderness Coefficient (TSC), Crown Ratio (CR), Crown Projection Area (CPA) and Site Index (SI) estimated. A total of 1,592 trees were enumerated and each tree per plot classified into four canopy layers as dominant, co-dominant, intermediate and suppressed. Data obtained were used for modelling and categorized into individual tree level, size class level and whole stand level with Maximum Likelihood Estimation (MLE) technique adopted in 3-parameter Weibull Probability Distribution Functions (WPDF). Data were analysed using descriptive statistics, ANOVA, correlation and regression analyses at α0.05. Growth variables exhibited significant variations among the canopy layers with the dominant canopy layer having the highest mean THT of 14.9±0.2m and intermediate canopy layer lowest with 7.8±0.1m. Stem volume (1.4±0.04m3) and BA (0.1±0.002m2) were also highest in the dominant canopy layer. Slenderness coefficient however was highest (80.6±1.1) within the suppressed canopy layer while crown ratio was highest (0.27±0.001) in intermediate canopy layer. There were positive relationships between the growth variables across the stands with coefficients of correlation (r) ranging from 0.01-0.98 for individual tree level and 0.41-0.91 for whole stand level. Similar results of UNIVERSITY OF IBADAN LIBRARY iii correlation between Weibull parameters and other growth variables at the size class level were significant with r ranging between -0.72 and 0.92 with location parameter „a‟ of the WPDF having the highest positive association of r = 0.92 with DBH. The growth-yield models were of the forms lnCR =-3.5507+0.6263lnTHT+0.1558CPA+10.2339A 1, R2 =0.98 for dominant layer, lnCR = -3.1922+0.6363CPA+7.6876A-1, R2 = 0.994 for intermediate layer, lnTHT= 0.4547+0.0032lnSQ+0.6757CPA+0.1052A-1, R2=0.989 for suppressed layer and lnTHT=0.5872+0.5348CPA+0.0567A-1 with R2= 0.996 for co-dominant layer respectively. The overall best model among individual, size and whole stand categories was found within the whole stand level with R2=0.999 and of exponential form: lnSV=-0.7759+0.0001SI+0.0005A-1 +0.9532lnBA. The best adjudged growth-yield model among the canopy layers was found within the co-dominant layer. The selected whole stand growth-yield model was suitable for both current and future prediction of major growth characteristics and productivity potentials of Pinus caribaea in southwestern Nigeria. Keywords: Pinus caribaea, Growth variables, Yield models, Tree canopy layers Word count: 489